2019
DOI: 10.1177/0972652719831549
|View full text |Cite
|
Sign up to set email alerts
|

Unique Calendar Effects in the Indian Stock Market: Evidence and Explanations

Abstract: Covering 20 years (1995–2015), the article ascertains the presence of the month-of-the-year effect in the Indian stock market, for the raw returns series as well as after adjusting for non-linearities of the market. Whether the effect is the same for portfolios of different sizes and values is also ascertained. The threshold generalised autoregressive conditionally heteroskedastic (TGARCH) model is employed to address non-linearity. The results suggest the presence of higher returns in November/December at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…However, an impulsive response that may occur due to financial disclosures by the firms, monetary news announcements, or psychological factors result in certain trading irregularities in the form of abnormally high or low calendar patterns; commonly known as calendar anomalies. Such observed inconsistencies are more evident in stock markets and have been analyzed in various studies (Harshita, Singh, & Yadav, 2019;Jaffe & Westerfield, 1985;Jones, Lee, & Apenbrink, 1991).…”
Section: Introductionmentioning
confidence: 94%
“…However, an impulsive response that may occur due to financial disclosures by the firms, monetary news announcements, or psychological factors result in certain trading irregularities in the form of abnormally high or low calendar patterns; commonly known as calendar anomalies. Such observed inconsistencies are more evident in stock markets and have been analyzed in various studies (Harshita, Singh, & Yadav, 2019;Jaffe & Westerfield, 1985;Jones, Lee, & Apenbrink, 1991).…”
Section: Introductionmentioning
confidence: 94%
“…One of the important explanations is the tax-loss selling theory, i.e. investors tend to sell stocks at a declining price at year-end to counterbalance capital gains by realizing capital losses, which could drive such stocks to earn comparatively higher returns in January (Harshita et al. , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2019). Another explanation for this effect could be the window dressing that institutional investors generally make (Lakonishok and Smidt, 1988; Harshita et al , 2019). Conversely, Fountas and Segredakis (2002) find no evidence for the January effect and its associated tax-loss selling hypothesis in the emerging stock markets context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have been reviewed in Kumar (2017) and based on the findings, the markets have achieved a higher degree of efficiency during the 1980s and 1990s. Others related studies on calendar effect can be found in Abalala & Sollis 2015, Harshita & Yadav (2019) and Saldanha & Desai (2019).…”
Section: Introductionmentioning
confidence: 98%